(untitled) (Scientific journal of the Fergana State University, 2026)
This study presents a preliminary evaluation of gliding-arc plasma for regenerating coked Ca-zeolite adsorbents previously used in natural gas purification. Thermal analysis revealed 24.7% total weight loss, indicating the presence of both soft and hard coke fractions. GAP treatment (2.5-15 min) enabled progressive mass reduction (up to 3.8%), accompanied by partial recovery of textural properties. The surface area increased from 84.3 m2/g (coked) to 98.4 m2/g after 15 min ( 79% of fresh sample), while total pore volume rose from 0.19 to 0.30 cm3g ( 80% of fresh). Mechanical stability tests confirmed that crush strength and attrition resistance remained largely unaffected by plasma treatment. Compared to conventional thermal regeneration, which often requires hours of heating, gliding-arc plasma achieved significant recovery within minutes, highlighting its potential as an energy-efficient and environmentally friendly regeneration method.